TIMOR-LESTE RECENTLY ADOPTS MIXED CURRICULUM OF INDONESIA AND EUROPEAN ECTS - Elizito de Almeida, João da Silva, Zeferino da Costa Brandão Sancha Francisca da Conceição , Adelio (JURNAL ILMU PENDIDIKAN, 2026)
East Timor, now referred to as Timor-Leste, gained independence as a sovereign country in the Asian region in 2002. Nonetheless, it endured much suffering and hardship caused by prolonged foreign occupations. Throughout the Indonesian occupation, the government of the state continue to use the previous curriculum established by the Indonesian government for all educational institutions, from primary to tertiary levels, in Timor-Leste. Consequently, the education systems are consistently utilized alongside the government, which has recently adopted blended European Credit Transfer and Accumulation System (ECTS) in its political policies. Therefore, the government via the Ministry of Education has a strategic plan to revamp the curriculum from 2011 to 2030, with the primary aim of establishing high-quality education in the contemporary global era. Although both curriculums are utilized together, they are highly beneficial and appropriate for education in Timor-Leste, fostering a practical implementation of culturally relevant education to achieve future innovations in the country’s development. This represents a pledge by the government in the sovereign state globally to the future of Timor-Leste. The children are asked to enter to school freely in the whole territory according to the Constitution. The reason why government with the commitment to mixed the curriculum into the education systems.